Social psychology : study guide - Brehm, Sharon S. (Houghton Mifflin, 1999)
Introduction. Doing social psychology research. The social self. Perceiving persons. Perceiving groups. Attitudes. Conformity. Group processes. Attraction and close relationships. Helping others...